STRATEGI PEMASARAN DALAM MEMPERTAHANKAN PELANGGAN (STUDI KASUS PADA HERBALIFE DI NC HAPPY SANGGAU) - Lisien Al, Alfonsus Ligouri; Octavia, Ayu Nurafni (Jurnal Ekonomi Sakti, 2024)
This research was conducted by Herbalife at NC Happy Sanggau. The purpose of this study was to reveal the Herbalife Marketing Strategy at NC Happy Sanggau in retaining customers. This research uses qualitative methods, using triangulation of data sources, namely observation, interviews, documentation. This research was conducted on 5 informants of owners, employees, and customers. The results of this study indicate that the strategy used in efforts to retain customers is to prioritize customer satisfaction. The Price offered is affordable and in accordance with the quality of service and Product quality. The Promotion used is direct Word of Mouth